Information Management against Excessive Stock Trading: More or Less? Or Both? - Moritz Mosenhauer (ZBW - Leibniz Information Centre for Economics, 2020)
This paper investigates tools to counter excessive stock trading and increase profits for private households participating in the stock market. Creating a stylised hold or trade-scenario in a computer laboratory experiment, I find that by solely changing the information the participants receive, trading activity can be reduced by roughly 30%, increasing trading profits by more than 0.55 percentage points on monthly net returns. In particular, I consider two information treatments. First, I provide the participants with additional information by giving detailed feedback on their actions and outcomes at every turn. Second, when considering whether to hold a given stock or trade it for another one, I restrict participants' information on the recent performance of their allocated stock. Both interventions lead to significant changes in behaviour. Additionally, the 2 2 experimental design reveals that the effects stack.
Keywords: G41; 330